การสะสมธาตุคาร์บอนในมวลชีวภาพเหนือพื้นดินของไม้ยืนต้นในพื้นที่ป่าชุมชนบ้านบุญเรือง ตำบลไหล่น่าน อำเภอเวียงสา จังหวัดน่าน - กุลธิดา ป้องมาลี (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Forest ecosystem is an important source of carbon dioxide storage by sequester atmospheric carbon dioxide through the photosynthetic process and store such carbon as biomass for mitigating climate change. Community forest is important source of carbon storage, but a few studies have been conducted. Therefore, this study aims to investigate aboveground biomass and carbon sequestration in aboveground biomass in the community forest belonged to Bun Rueang village, Lainan subdistrict Wiang Sa district, Nan province. Field data were collected in 4 sampling plots of 40×40 sq.m. Species, diameter at breast height and height were recorded, and then used to calculate the aboveground biomass by allometric equation. Carbon storage of plants were indicated by 50% of the aboveground biomass. The results showed that there were 1,038 trees (1,621 trees/ha). They could be classified into 22 families, 39 identified species, and 9 unidentified species. Total carbon storage in aboveground biomass was 8.70±2.43tC/ha. The results demonstrated that community forests at Bun Rueang village had lesser carbon storage compared with deciduous forest in the same area (47.89±12.58 tC/ha, reported by Chengsutdha, 2555). This might because most of the trees in this community forest are small size. Thus, community need to study about useful of community forest and how to keeping community forest such as firebreaks, ordained a tree and utilization of non-timber forest products etc. That might be help the small tree to survive and grow into the large tree in the future.